Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Minat Berkunjung Kembali Melalui Kepuasan Pasien Rumah Sakit Lukas - Sulaiha, R.A Annisa Putri; Setiyarini, Triana (Jurnal Kajian Ilmu Manajemen (JKIM), 2025)
The rise in the socioeconomic status of society has increased awareness and demand for quality healthcare services. Consequently, the healthcare service industry, particularly hospitals, must meet these needs by improving their facilities and service quality. Lukas General Hospital (RSU Lukas) faces several challenges, especially in outpatient services, such as patient dissatisfaction with certain services, lack of facilities, and competition with other hospitals offering similar services. These challenges may ultimately affect patient loyalty and their intention to revisit RSU Lukas Bangkalan. This study aims to analyze the influence of service quality and facilities on patients' intention to revisit, with patient satisfaction serving as a mediating variable at Lukas Hospital, Bangkalan. Data were collected through surveys and questionnaires distributed to 140 patients and hospital visitors and analyzed using Partial least square (PLS), including tests for outer and inner model coefficients and hypothesis testing. The results indicate that service quality and facilities significantly influence patient satisfaction, which subsequently affects patients' intention to revisit. Patient satisfaction was found to mediate this relationship, showing that the more satisfied patients are with the services and facilities provided, the greater their likelihood of revisiting the hospital. This study concludes that improving service quality and hospital facilities is a critical factor in enhancing patient satisfaction and loyalty. Future studies are recommended to explore additional factors, such as cost and accessibility.